2021
DOI: 10.1093/mnras/stab1443
|View full text |Cite
|
Sign up to set email alerts
|

Radio relics in PSZ2 G096.88+24.18: a connection with pre-existing plasma

Abstract: Giant radio relics are arc-like structures of diffuse, non-thermal synchrotron radiation that trace shock waves induced by galaxy cluster mergers. The particle (re-)acceleration mechanism producing such radio relics is unclear. One major open question is whether relics can be formed directly from a population of thermal seed electrons, or if pre-existing relativistic seed electrons are required. In some cases AGN can provide such a population of sub-GeV electrons. However, it is unclear how common this connect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
1
15
1
Order By: Relevance
“…For radio halos, these systems include Abell 3562 (Venturi et al 2003;Giacintucci et al 2005 G049.32+44.37, PSZ2 G179.09+60.12, and PSZ2 G172.63+35.15 (Botteon et al 2022). For relics, the low-mass systems hosting relic(s) that have been reported in the literature are ZwCl 0008.8+5215 (Feretti et al 2012;van Weeren et al 2011), Abell 1240(Kempner & Sarazin 2001Bonafede et al 2009;Hoang et al 2018), Abell 3376 (Bagchi et al 2006), PSZ1 G096.89+24.17 (De Gasperin et al 2014;Jones et al 2021), Abell 168 (Dwarakanath et al 2018), Abell 1904(van Weeren et al 2021), PSZ2 G080.16+57.65, PSZ2 G099.48+55.60, PSZ2 G048.10+57.16, PSZ2 G165.46+66.15, and PSZ2 G057.61+34.93 (Botteon et al 2022).…”
Section: Source Classificationmentioning
confidence: 97%
“…For radio halos, these systems include Abell 3562 (Venturi et al 2003;Giacintucci et al 2005 G049.32+44.37, PSZ2 G179.09+60.12, and PSZ2 G172.63+35.15 (Botteon et al 2022). For relics, the low-mass systems hosting relic(s) that have been reported in the literature are ZwCl 0008.8+5215 (Feretti et al 2012;van Weeren et al 2011), Abell 1240(Kempner & Sarazin 2001Bonafede et al 2009;Hoang et al 2018), Abell 3376 (Bagchi et al 2006), PSZ1 G096.89+24.17 (De Gasperin et al 2014;Jones et al 2021), Abell 168 (Dwarakanath et al 2018), Abell 1904(van Weeren et al 2021), PSZ2 G080.16+57.65, PSZ2 G099.48+55.60, PSZ2 G048.10+57.16, PSZ2 G165.46+66.15, and PSZ2 G057.61+34.93 (Botteon et al 2022).…”
Section: Source Classificationmentioning
confidence: 97%
“…This relic is connected, at least in projection, to an AGN (see van Weeren et al 2021, for more details), which could have had an effect on the relic's brightness. Such an effect has been observed in other relics, such as PSZ2 G096.88+24.18 (Jones et al 2021). However, PSZ2 G089.52+62.34 is also a low-mass cluster, where we observe very few relics and therefore the correlation is poorly constrained.…”
Section: Low-power Rrsmentioning
confidence: 48%
“…Evidence of turbulence in the downstream regions of relics has been discovered in some clusters. For example, Kale et al (2012) and Jones et al (2021) found patchy polarised emission in the Abell 3376 and PSZ2 G096.88+24.18 relics, respectively, which they each attributed to turbulence. Di Gennaro et al (2021) performed an extensive analysis of the polarisation structure in the Sausage relic using RM-synthesis.…”
Section: Downstream Relic Widthmentioning
confidence: 99%
“…For PSZ1 G096.89+24.17, we used flux density measurements at 140 MHz and 1.5 GHz from Jones et al (2021) and we computed 380 and 610 MHz flux densities from proprietary GMRT observations (Rajpurohit et al in preparation). For El Gordo, we measured the flux density at 325 and 610 MHz using archival observations (observed during 2017), and we used the 2.1 GHz measurement from Lindner et al (2014).…”
Section: Appendix A: Broadband Integrated Radio Spectramentioning
confidence: 99%